PEMBERDAYAAN KELOMPOK PKK BANJAR LEBAH DESA SUMERTA SEBAGAI KADER SADAR GIZI DALAM MENJAGA SISTEM IMUN TUBUH UNTUK MENGHADAPI PANDEMI COVID-19 - Indraningrat, Anak Agung Gede; Wijaya, Made Dharmesti; Sri Masyeni, Dewa Ayu Putri (Buletin Udayana Mengabdi, 2020)
Good and sufficient nutritional intakes are prerequisite to build a strong immune system against infectious diseases especially during the pandemic of COVID-19 that spread out widely since the early year of 2020. Currently socialization about COVID-19 have been emphasized on the preventive aspects such as washing hand with soap properly, using face mask and applying social distancing. However, these preventive aspects have not much focused on nutritional aspects. In order to build awareness of society on good nutritional intakes, this community service focused to build a group of cadres in collaboration with the women group (PKK) of Banjar Lebah Desa Sumerta Denpasar.  The method of socialization was conducted via face to face meeting by still applying health protocols such as using face mask, washing hand with soap and physical distancing. Evaluation of the community service activity showed that cadres have displayed significant understanding about good nutritional intakes as indicated by increasing of post-test grades to 35% compared to the initial pre-test grades. These cadres were also successfully made yoghurt as the example of nutritional foods that can be consumed daily. In the future, these cadres were expected to actively socializing the importance of good nutritional intakes for their neighbourhood especially during the pandemic of COVID-19. Keywords: COVID-19, nutritional awarness, pandemic